Electrical properties and AC susceptibility of CdTe added Tl2Ba2CaCu2O8-δ superconductor - K. Muhammad-Aizat,; R. Abd-Shukor, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Information on semiconductor/superconductor interface is important in fabricating devices of such hybrid systems. In this paper the electrical properties and AC susceptibility of Tl2Ba2CaCu2O8 (Tl-2212) superconductor added with CdTe semiconductor are reported. Samples with nominal starting composition Tl2Ba2CaCu2O8(CdTe)x with x = 0 to 0.20 weight percent (wt. %) have been prepared by the solid-state reaction method. X-ray diffraction patterns showed essentially the Tl-2212 phase with presence of impurities (CuO and Tl2Ba2CuO6) for x ≥ 0.05 wt. % but did not change the Tl-2212 structure which is tetragonal with lattice parameter a = b ≠ c. The critical onset temperature, Tc-onset for all samples was between 104 and 108 K while the critical zero resistance temperature, Tc-zero was from 93 to 95 K. The superconducting transition determined by AC susceptibility measurement showed Tcχ’ between 101 and 103 K. The peak temperature, Tp of the imaginary part of the susceptibility χ” decreased for x = 0.05 and then increased for x > 0.05. This indicated that the superconducting grains were strongly coupled for x > 0.05 as a result of CdTe addition. The intergrain critical current density, Jc at Tp for the x = 0.2 sample Jc (Tp = 95 K) = 23 A cm-2 was the highest among all samples. This sample also showed the highest Tp indicating CdTe improved the flux pinning of the Tl-2212 phase. This result can be useful in the fabrication of semiconductor/superconductor (Tl-2212) hybrid devices.